2022
DOI: 10.3390/toxics10050207
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Exposure and Risk of Rheumatoid Arthritis: A Systematic Review and Meta-Analysis

Abstract: Rheumatoid arthritis (RA) is a disease that affects people all over the world and can be caused by a variety of factors. Exposure to pesticides is one of the risk factors for the development of RA. However, the evidence of exposure to pesticides linked with the development of RA is still controversial. This study aimed to investigate the association between exposure to pesticides and RA by a systematic review of relevant literature and a meta-analysis. Full-text articles published in PubMed, Web of Science, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Exposure to these chemicals can cause both acute and chronic health consequences (4). Several studies have shown that exposure to OP was associated with chronic diseases such as asthma, rheumatoid arthritis, cancers, Alzheimer's disease, Parkinson's disease, and cognitive impairment (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to these chemicals can cause both acute and chronic health consequences (4). Several studies have shown that exposure to OP was associated with chronic diseases such as asthma, rheumatoid arthritis, cancers, Alzheimer's disease, Parkinson's disease, and cognitive impairment (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms through which toxic chemical exposure may contribute to MS onset remains are not completely understood. Exposure to weed control agents can alter immune response, potentially resulting in inflammatory diseases, including rheumatoid arthritis and systematic lupus erythematosus 23 24. Glyphosate (RoundUp) can induce the nuclear factor-kappa B ( NF-κB ) signalling pathway in several human cell types14 15 25 inducing gene expression of proinflammatory cytokines like TNF- α, IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various risk factors for the development of RA, a systematic review of relevant literature between 1956 and 2021 and a meta-analysis were conducted to investigate the association between pesticide exposure and RA [ 116 ]. A total of eight studies were eligible for inclusion (two cohort studies, four case–control studies, and two cross-sectional studies) and showed that exposure to insecticides (especially fonofos, carbaryl, and guanidines) contributes to an increased risk of RA.…”
Section: Immune-mediated Inflammatory Disease Development Is Enhanced...mentioning
confidence: 99%